ENGLISH INTERJECTIONS AS A WORD CLASS: A TRI-STRATAL DESCRIPTION - Jing, Yi (Indonesian Journal of Applied Linguistics, 2017)
Traditionally known as interjections, the highly conventionalized linguistic forms like aha, hey, ouch, oh, sh, etc. have not been recognized as a word class in Systemic Functional Linguistics (SFL). A proximate word class that does get acknowledged in SFL is the continuative (typically represented by well, oh, yes, no and now), while other members in the traditional class of interjections tend to be treated as bi-stratal forms in language, if not protolanguage. Studies that are non-SFL driven have affiliated interjections with routines, formulae, discourse particles, discourse markers, etc. Such terminological complexity can be solidified and cleared if interjections are perceived as a word class under the SFL framework. The present paper, thus, proposes to discuss interjections across the language strata – from below (phonology and graphology), from around about (lexicogrammar), and from above (semantics, in terms of the metafunctions). This holistic view will contribute to linguistic description of interjections and help enhance the understanding of interjections as a word class.